Pengaruh Usia Penyapihan dan Pengetahuan Ibu terhadap Status Gizi Anak di Puskesmas Johan Pahlawan - Makfirah, Daral; Mulyani, Itza; Khairunnas, Khairunnas; Muhsin, Sri Wahyuni; Marniati, Marniati (Medan Resource Center, 2024)
Nutritional issues in children aged 0-59 months are critical, as this age group is particularly vulnerable to dietary changes affecting nutritional status. Weaning, defined as the transition from breastfeeding to solid foods, and maternal knowledge are considered key factors influencing child nutrition. This study aims to examine the impact of weaning age and maternal knowledge on the nutritional status of children aged 0-59 months in the Johan Pahlawan Public Health Center area. A cross-sectional design with simple random sampling was used, involving 95 respondents. Data collection included questionnaires and nutritional status measurements. Chi-Square analysis revealed a significant relationship between maternal knowledge and child nutritional status (p=0.009), while no significant relationship was found between weaning age and nutritional status (p=0.126). These findings suggest that enhanced maternal knowledge plays a crucial role in improving child nutritional outcomes, whereas weaning age does not have a significant effect.